2013
DOI: 10.1007/978-1-62703-327-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Human-Like Glycosylation to Produce Therapeutic Glycoproteins Based on 6-Linked Sialylation in CHO Cells

Abstract: When recombinant glycoproteins for therapeutic use are to be produced on an industrial scale, there is a crucial need for technologies that can engineer fast-growing stable cells secreting the protein drug at a high rate and with a defined and safe glycosylation profile. Current cell lines approved for drug production are essentially from rodent origin. Their glycosylation machinery often adds undesired carbohydrate determinants which may alter protein folding, induce immunogenicity, and reduce circulatory lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/6/15 11:56 AM Rodent cell lines such as CHO are not able to attach terminal sialic acid to N-glycans via an α-2,6-linked glycosidic bond [164]. In order to achieve an efficient formation of α-2,6-linked sialylation, CHO host cells were transfected with ST6Gal [164].…”
Section: Glycoengineering Methods Targeting the N-glycan Processing Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/6/15 11:56 AM Rodent cell lines such as CHO are not able to attach terminal sialic acid to N-glycans via an α-2,6-linked glycosidic bond [164]. In order to achieve an efficient formation of α-2,6-linked sialylation, CHO host cells were transfected with ST6Gal [164].…”
Section: Glycoengineering Methods Targeting the N-glycan Processing Mmentioning
confidence: 99%
“…In order to achieve an efficient formation of α-2,6-linked sialylation, CHO host cells were transfected with ST6Gal [164].…”
Section: Glycoengineering Methods Targeting the N-glycan Processing Mmentioning
confidence: 99%
“…Some of them regard the design of the expression vector and, for example, make use of inducible promoters and/or epigenetic regulators to increase and prolong transgene expression while decreasing toxicity of the expressed recombinant protein [13], [14], [15], [16]. Others approaches aim at manipulating pathways through cell engineering, in order to improve stress resistance, cell viability or to achieve better glycosylation profiles [7], [17]. Despite much progress has been made in this field, clonal variability and instability are still important issues that need to be addressed, particularly when production on large scales (1000's liters) is required.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the progress of systems biology, it will be possible to manipulate cells to introduce entire new molecular pathways ( e.g. human-like glycosylation) [17], [29]. The rational engineering of such robust and high-performing cells for specific applications can lead to a catalog of different cell lines, each optimized to tackle specific targets.…”
Section: Introductionmentioning
confidence: 99%
“…They reported altered glycan‐type ratios in the recombinant cell line. Maï et al reported a host CHO cell line with a St6gal1 minigene integrated to overexpress ST6GAL1, and they generated adherent clones secreting hypersialylated proteins …”
Section: Introductionmentioning
confidence: 99%